1999
DOI: 10.1051/forest:19990702
|View full text |Cite
|
Sign up to set email alerts
|

Phytophthora species in oak forests of north-east France

Abstract: -Phytophthora species were surveyed from the end of 1997 through July 1998 in oak forests in NE France. Healthy (Amance)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
135
5
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(151 citation statements)
references
References 14 publications
10
135
5
1
Order By: Relevance
“…A single unique Phytophthora isolate was obtained in 1998 from soil under oak trees in Illwald Forest of Alsace, France (Hansen and Delatour 1999). In 2003, P1055 was informally designated as P. taxon oaksoil by Brasier et al (2003a) and was reported to be sexually sterile.…”
Section: Discussionmentioning
confidence: 99%
“…A single unique Phytophthora isolate was obtained in 1998 from soil under oak trees in Illwald Forest of Alsace, France (Hansen and Delatour 1999). In 2003, P1055 was informally designated as P. taxon oaksoil by Brasier et al (2003a) and was reported to be sexually sterile.…”
Section: Discussionmentioning
confidence: 99%
“…Several new Phytophtora ssp. have recently been described and suggested to be involved in European oak declines [82,90,[92][93][94][95][96]. Although these species act as primary pathogens, their pathogenicity generally seems to be too low to induce mortality alone, yet Phytophthora spp.…”
Section: Possible Role Of Root Pathogens In Declines Associated Withmentioning
confidence: 99%
“…Also commonly recovered are Clade 6 Phytophthora species which are hypothesised as having a prevalently saprophytic lifestyle (Brasier et al 2003a;Hansen et al 2012) as supported by their presence and dominance in water surveys (e.g. Hansen and Delatour 1999;Reeser et al 2011). Under favourable conditions some of these Clade 6 species, such as P. inundata, P. taxon PgChlamydo, P. gonapodyides and P. lacustris (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Under favourable conditions some of these Clade 6 species, such as P. inundata, P. taxon PgChlamydo, P. gonapodyides and P. lacustris (e.g. Hansen and Delatour 1999;Greslebin et al 2005;Smith et al 2009;Randall 2011;Reeser et al 2011;Nechwatal et al 2012), can be aggressive tree pathogens (Brasier et al 2003b;Brown and Brasier 2007;Jung 2009). P. inundata has been isolated from dying native vegetation in Western Australia (WA) (Stukely et al 2007).…”
Section: Introductionmentioning
confidence: 99%